The Association Between Prenatal Maternal Stress and Adolescent Affective Outcomes is Mediated by Childhood Maltreatment and Adolescent Behavioral Inhibition System Sensitivity - Sebők-Welker Tünde Éva; Kovács-Posta Evelyn Csenge; Ágrez Kristóf; Rádosi Alexandra; Zubovics Evelin Alexa; Réthelyi János; Ulbert István; Pászthy Bea; Bunford Nóra (CHILD PSYCHIATRY & HUMAN DEVELOPMENT, 2024)
Prenatal maternal stress is linked to offspring outcomes; however, there is little research on adolescents, behavioral, transdiagnostic outcomes, or the mechanisms through which relations operate. We examined, in N = 268 adolescents ( M age = 15.31 years; SD = 1.063; 57.8% boys) whether prenatal maternal stress is associated with adolescent affective outcomes; whether this association is mediated, serially, by childhood home atmosphere and adolescent behavioral inhibition system (BIS) sensitivity; and whether mediational effects are moderated by adolescent attention-deficit/hyperactivity disorder or maternal internalizing symptomology. Prenatal maternal daily stress and major life events were associated with adolescent outcomes through childhood negative atmosphere/neglect and BIS sensitivity, with no evidence of moderation. Results have implications regarding the effect of prenatal maternal stress on offspring outcomes and regarding corresponding sensitive periods.